Characterization of cross frequency couplings produced by harmonic and non-harmonic frequency bands during seizure activity from intracerebral recordings in patients candidate to epilepsy surgery - Dellavale Clara, Hector Damian; Urdapilleta, Eugenio; Cámpora, Nuria Elide; Velarde, Osvaldo Matias; Kochen, Sara Silvia; Mato, German (Society for Neuroscience, 2018)
Fil: Dellavale Clara, Hector Damian. Comisión Nacional de Energía Atómica. Unidad Ejecutora Instituto de Nanociencia y Nanotecnología. - Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad Ejecutora Instituto de Nanociencia y Nanotecnología; Argentina